2017
DOI: 10.1186/s13046-017-0579-0
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic acid sensitizes gemcitabine efficacy in pancreatic cancer by reducing the expression of ribonucleotide reductase subunit-M2 (RRM2)

Abstract: BackgroundPancreatic cancer is susceptible to gemcitabine resistance, and patients receive less benefit from gemcitabine chemotherapy. Previous studies report that gambogic acid possesses antineoplastic properties; however, to our knowledge, there have been no specific studies on its effects in pancreatic cancer. Therefore, the purpose of this study was to explore whether increases the sensitivity of pancreatic cancer to gemcitabine, and determine the synergistic effects of gambogic acid and gemcitabine agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 52 publications
3
56
0
1
Order By: Relevance
“…Nampt inhibitor (FK866) reversed this resistance to sensitivity [53]. Additionally, gemcitabine also promotes the expression of the ribonucleotide reductase M2 (RRM2) subunit in pancreatic cancer cells through the ERK/E2F1 pathway, promoting deoxyribonucleotide biosynthesis and inhibiting gemcitabine-induced DNA damage [153,154]. CG-5, a glucose transporter inhibitor, inhibits E2F1 expression and enhances gemcitabine efficacy in pancreatic cancer cells [153].…”
Section: Chemoresistance and Metabolismmentioning
confidence: 99%
“…Nampt inhibitor (FK866) reversed this resistance to sensitivity [53]. Additionally, gemcitabine also promotes the expression of the ribonucleotide reductase M2 (RRM2) subunit in pancreatic cancer cells through the ERK/E2F1 pathway, promoting deoxyribonucleotide biosynthesis and inhibiting gemcitabine-induced DNA damage [153,154]. CG-5, a glucose transporter inhibitor, inhibits E2F1 expression and enhances gemcitabine efficacy in pancreatic cancer cells [153].…”
Section: Chemoresistance and Metabolismmentioning
confidence: 99%
“…The combination of GA and other chemotherapy agents has been widely used to improve the therapeutic effects against various cancers such as osteosarcoma, pancreatic and lung cancers [639,653,663,664]. Cisplatin resistance is a main clinical problem for the treatment of lung cancer, and the treatment of cisplatin with GA is shown to enhance apoptosis and decrease the cisplatin resistance index in human NSCLC cisplatin-resistance A549/ DDP cells [663].…”
Section: Gambogic Acid (Ga)mentioning
confidence: 99%
“…Previous studies have revealed that ZFP36 is a downstream gene in the EGFR and ERK signaling pathway [32], which is also required for the self-renewal of cancer stem cells in addition to regulating proliferation and survival [31]. KEGG pathway analyses and related studies have reported that GA can downregulate the EGFR and ERK signaling pathway [46]. Furthermore, our results revealed that GA could increase the expression of ZFP36 by inhibiting the EGFR/ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 56%